ヒガシ ナンキョク ノ ヤマト サンミャク オヨビ インセキ ヒョウゲン ジョウ ニ オケル コウクウ ジキ ソクリョウ - 渋谷, 和雄; シブヤ, カズオ; 田中, 晶子; タナカ, アキコ; 真部, 允宏; マナベ, ミツル; Shibuya, Kazuo; Tanaka, Akiko; Manabe, Mitsuru (1987)
P(論文) やまと山脈およびいん石氷原の地域で, 1975年および1980年に航空磁気測量を行った。これらの観測結果を解析して, 基盤岩の地質, 帯磁率, 地形などとの関連性を検討した結果, 観測された地磁気異常分布は, 氷床下の基盤の地形と最も関係が深いと解釈しうることがわかった。 Aeromagnetic surveys were conducted in the Yamato Mountains and the Meteorite Ice Field region in 1975 and 1980,using Cessna A185F and Pilatus Porter PC-6 aircrafts respectively. Distribution of geomagnetic anomaly in this area obtained from those surveys is thought to be correlated mostly with the subglacial topography other than types or magnetic susceptibility of bedrocks. departmental bulletin paper